(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
Objective: A study of the complications associated with RDS in a group of preterm infants weighing less than 1500 grams compared to another group of preterm infants, with similar birthweight, without RDS. Methods: An observational descriptive study included all the preterm infants with VLBW and ELBW, admitted to the Neonate unit at Tishreen University Hospital, during the study period from 1 November 2017 to 1 November 2018. Study sample was divided into two groups: VLBW and ELBW preterm infants with RDS VLBW and ELBW preterm infants without RDS. Results: A statistical study was conducted for 72 preterm infants. RDS was found in 38.9%. Hospitalization period median was longer in preterm infants without RDS (20days) versus RDS patients (12days). Mean Gestational age in RDS group was 27.6 weeks, while it was 30.8 weeks in the other group (p-value0.001). Mean birthweight in RDS group was 1021 (+/- 403) grams, and 1247 (+/-230) grams in the other group. RDS was found more often in Gestational ages (GA) less than 32 weeks, and most of the patients with RDS were born with gestational ages less than 28 weeks (53. 57%).Neonatal sepsis was the most common complication (48.6%) then Apnea of preterm (41.6%) and Intraventricular hemorrhage (IVH) 22.22%. IVH was more frequent in RDS group. 32 of preterm infants died (44%), 26.4% (19 patient) died of Respiratory failure .RDS mortality was 33.3% (24 patients). Mortality was higher in preterm infants with GA less than 32 weeks. RDS mortality happened more often in preterm born with GA less than 28 weeks (60%). هدف الدراسة: دراسة الاختلاطات المرافقة لتناذر العسرة التنفسية عند الخدج RDS بالمقارنة مع مجموعة من الخدج المولودين بأوزان أقل من 1500 غراما، ممن لم يصابوا ب RDS. دراسة نسبة الوفيات المسببة بكل اختلاط على حدة عند مرضى متلازمة العسرة التنفسية ومقارنة النتائج مع مجموعة المراقبة. طرائق البحث ومواده: شملت الدراسة جميع المواليد ال خدجVLBW وELBW في شعبة امراض الوليد والخديج بين تشرين الثاني 2017 حتى تشرين الثاني 2018. دراسة وصفية رصدية وتم تقسيم عينة الدراسة لمجموعتين: خدج VLBW وELBW مصابين ب RDS خدج VLBW وELBW غير مصابين ب RDS تم وضع تشخيص RDS اعتمادا على العلامات السريرية واجراء صورة بسيطة للصدر حسب التعريف. تمت مراقبة المجموعتين سريريا، مخبريا وشعاعيا وتسجيل الاختلاطات الحاصلة لدى كل مجموعة على حدة النتائج: شملت عينة الدراسة 72 خديجاً، 43 ذكراً و29 أنثى (1.4: 1). تطورت متلازمة العسرة التنفسية ال RDS عند حوالي 38،9%من عينة الدراسة. كان متوسط مدة الاستشفاء عند المرضى الذين لم يطوروا الـ RDS أطول (20يوماً) مقارنة بمرضى RDS (12يوماً). كان متوسط العمر الحملي للمصابين بال RDS: 27.6 أسبوعاً حملياً، بينما كان متوسط اعمار غير المصابين 30.8 أسبوعاً حملياً (P-Value 0.001). كان متوسط وزن الولادة لمرضى (±.430.3) 1021 RDS غراما بينما كان متوسط وزن الولادة للمجموعة المقابلة (±230.1)1247 غراما. لوحظ أن ال RDS كانت أكثر مشاهدة لدى الأعمار الحملية الأقل من 32 أسبوعاً حملياً حيث مثلت 85.7% من الحالات واغلب الحالات كانت مع الاعمار الحملية الأقل من 28 أسبوعاً حملياً حيث مثلت 53.57% من الحالات. الانتان هو أكثر الاختلاطات مشاهدة في عينة الدراسة حيث مثَل 48.61% تلاه نوب توقف التنفس بنسبة 41.66%، ثم النزف ضمن البطينات الدماغية والذي كان أكثر مشاهدة لدى مرضى RDS مقارنة بالمجموعة المقابلة. حدثت الوفاة عند (32) حالة بنسبة 44% من مجمل عينة الدراسة من بينها (19) حالة بنسبة 26.4% بسبب القصور التنفسي وكان الاختلاط الأهم لحدوث الوفاة، وبلغت وفيات (24) RDS حالة، 33.3% من مجمل عينة الدراسة. لاحظنا ارتفاع معدل الوفيات لدى الأعمار الحملية الأقل من 32 أسبوعاً حملياً، واغلب الحالات كانت مع الاعمار الحملية الأقل من 28 أسبوعاً حملياً حيث مثلت 53.13 % من الحالات، وأن معظم وفيات RDS كانت لدى الخدج بعمر حملي أقل من 28 أسبوعاً بنسبة 60 %.